'For the benefit of our nation': unstable soft power in the 2018 men's World Cup in Russia. Issue 4 (1st October 2020) - Wolfe, Sven Daniel
ABSTRACT: Situated at the intersection of the literatures on soft power and mega-events, this paper explains the production and evolution of the dominant narratives behind the 2018 Men's Football World Cup in Russia. It begins from the premise that there are multiple unexplored dimensions to the concept of soft power and proposes three advancements: the existence of multiple audiences for soft power narratives, the necessity of examining soft power aspirations in the context of hard power constraints, and the investigation of both of these dimensions with a view that acknowledges the role of time. Exploring both externally and internally targeted narratives, this paper demonstrates not only the attempts by Russian authorities to construct hegemonic ideology among the domestic population, but also reveals how the interplay of hard power and soft power concerns changed these narratives over time.